Abordagem sistêmica do uso de lodo de ETE e ETA em pavimentação - Ferreira, Gustavo Oliveira (Universidade Federal de São Carlos, 2021)
Research performed from the beginning of the last decade has evaluated the potential allocation of both the sludge water treatment (ETA) and Wastewater Treatment Plant (WWTP) in the asphalt pavement layers and coating. For this purpose, different proportions of sludge in the mixed material portion have been studied, at different values of total sludge solids resulting from the thermal drying method obtained, or even in natura, being tested with or without stabilizing additives. Thus, the present work aims to analyze the research that proposes the possibility of disposal of WWTP and ETA sludge in paving, through a systematic bibliographic review, in which we sought to define the current state of the art on the subject, and from from this, carry out the compilation and analysis of the results obtained from the literature. . For this purpose, the information was organized through tables and comparative graphs between the researches carried out, to analyze the results obtained, focusing mainly on the type of sludge used; in the characterization (chemical, physical and mechanical) of this sludge; in percentages of sludge in the mixture under the aid of physical and mechanical parameters established by DNIT for each pavement layer and the types of traffic in which the use of sludge was proposed. When analyzing selected studies from the literature, within the pre-established criteria, it was found that the characterization parameters, percentages of sludge in the mixture and sample preparation methods are distinct and without a pattern followed by all, which depends more from the location of the ETA or ETE . It was also observed that the percentages of sludge used in the mixtures are diverse and without prior justification for application, but all studies evaluated in this work were successful in paving application, at least technically, in at least one of the mix configurations used. . It was noted that the environmental issue was observed in a minority of studies, however, the leaching and solubilization tests, carried out in some studies, were favorable. A greater inclination was observed in the use of calcined ETE sludge for paving, and the use of energy to remove water from the sludge by mechanical means was not evaluated in the surveys, and should be an important aspect in the intuition of computing monetary expenses in function of the energy consumed to raise this temperature and, in this way, to advance one more stage of analysis of the viability of using ETA and ETA sludge, in real scale, in the paving.
Systemic approach to the use of STP and WTP sludge in paving
Keywords: Lodo de ETA; Lodo de ETE; Pavimentação; Destinação; Usos benéficos; WTP sludge; STP sludge; Paving; Beneficial uses; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS::ENGENHARIA SANITARIA